Ideologem of enemy in the demagogic texts of post-revolutionary newspapers of Kazakhstan (Eurasian Journal of Philology Science and Education, 2016)
For understanding the current state of the Russian language it is necessary to examine the past of this language, because totalitarian language made a forced impact on linguistic consciousness. Newspaper is a channel through which the effective impact of totalitarian ideology on the public consciousness was implemented.The observation of the compressive demagogic texts from the Kazakhstani newspapers («Golos Semirechja», «Dzhetysuyskaya iskra», «Turkestansky Communist») showed that each such text conveys a certain ideologem: it contains a combination of two or more ideologies – judgments prescribed by totalitarian system as the official dogmas. One of the most common ideologies is the ideologem of confrontation on the basis of which the picture of the new world is simulated. It is introduced as mandatory and is motivated by a number of extra-linguistic factors: the revolution, class contradictions, external threat, internal threat, reaction victory. The ideologem of enemy is identified and described in this article. It also includes the ideology of class (class struggle), although the image of the enemy is much broader than concept of the class enemy.
Keywords: еnemy; predicate; ideologem; newspaper; totalitarian lan¬guage; revolution; semantics; demagogic texts.